The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1038/jhg.2011.13
|View full text |Cite
|
Sign up to set email alerts
|

Association of the arginine vasopressin receptor 1A (AVPR1A) haplotypes with listening to music

Abstract: Music is listened in all cultures. We hypothesize that willingness to produce and perceive sound and music is social communication that needs musical aptitude. Here, listening to music was surveyed using a web-based questionnaire and musical aptitude using the auditory structuring ability test (Karma Music test) and Carl Seashores tests for pitch and for time. Three highly polymorphic microsatellite markers (RS3, RS1 and AVR) of the arginine vasopressin receptor 1A (AVPR1A) gene, previously associated with soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 39 publications
0
57
0
2
Order By: Relevance
“…Because also vasopressin has strong connections with sociality [59], spatial and social memory [60,61], as well as with higher cognitive functions such as memory and learning in humans and other mammals [62], a series of studies started to investigate the role of vasopressin also in human music and dance. Such a coalition has been reported in several studies: the gene responsible for vasopressin receptor, AVPR1a, was associated with the dance phenotype [63], musical short-term memory [64], musical skills [65], and lifelong active listening to music [66]. Similarly, intranasal administration of vasopressin increased musical short-term memory performances [67].…”
Section: Vasopressin Courtship and Musicmentioning
confidence: 88%
“…Because also vasopressin has strong connections with sociality [59], spatial and social memory [60,61], as well as with higher cognitive functions such as memory and learning in humans and other mammals [62], a series of studies started to investigate the role of vasopressin also in human music and dance. Such a coalition has been reported in several studies: the gene responsible for vasopressin receptor, AVPR1a, was associated with the dance phenotype [63], musical short-term memory [64], musical skills [65], and lifelong active listening to music [66]. Similarly, intranasal administration of vasopressin increased musical short-term memory performances [67].…”
Section: Vasopressin Courtship and Musicmentioning
confidence: 88%
“…1 In another association study involving AVPR1A and SLC6A4 polymorphisms, Ukkola-Vuoti et al (2011) investigated the music listening habits of 31 Finnish families using surveys. Family-based association analysis revealed positive associations between AVPR1A haplotypes and active music listening.…”
Section: Summary Of the Review Findingsmentioning
confidence: 99%
“…Furthermore, this process may feed into intergenerational cultural transmission entailing musical as well as general cultural values. Another study showed that music listening was associated with neurobiological pathways affecting social affiliation and communication (Ukkola-Vuoti et al, 2011). In a family-based association analysis of Finnish families, the arginine vasopressin receptor 1A (AVPR1A) gene haplotypes were positively associated with active current and lifelong listening to music.…”
Section: Introductionmentioning
confidence: 99%